B cells and the stressed brain: emerging evidence of neuroimmune interactions in the context of psychosocial stress and major depression - Engler-Chiurazzi, Elizabeth (Frontiers in Cellular Neuroscience, 2024)
The immune system has emerged as a key regulator of central nervous system (CNS) function in health and in disease. Importantly, improved understanding of immune contributions to mood disorders has provided novel opportunities for the treatment of debilitating stress-related mental health conditions such as major depressive disorder (MDD). Yet, the impact to, and involvement of, B lymphocytes in the response to stress is not well-understood, leaving a fundamental gap in our knowledge underlying the immune theory of depression. Several emerging clinical and preclinical findings highlight pronounced consequences for B cells in stress and MDD and may indicate key roles for B cells in modulating mood. This review will describe the clinical and foundational observations implicating B cell-psychological stress interactions, discuss potential mechanisms by which B cells may impact brain function in the context of stress and mood disorders, describe research tools that support the investigation of their neurobiological impacts, and highlight remaining research questions. The goal here is for this discussion to illuminate both the scope and limitations of our current understanding regarding the role of B cells, stress, mood, and depression.